Effects of benzylaminopurine and naphthalene acetic acid on proliferation and shoot growth of pineapple (Ananas comosus L. Merr) in vitro - Al-Saif, A.M.; Hossain, A.B.M.S.; Taha, Rosna Mat (Academic Journals, 2011)
This study was conducted to evaluate the pineapple regeneration and shoot growth as affected by 6-benzylaminopurine (BAP) at 2.0 mg/l and naphthalene acetic acid (NAA) at 0.2 mg/l in vitro. BAP and NAA at the concentration of 2.0 and 0.2 mg/l were used in this study. BAP at 2.0 mg/l significantly affected the production of shoots per explant, shoot length and weight. Total shoot length was higher in BAP (2 mg/l) than in control (MS medium without hormone) and NAA (0.2mg/l) after 10, 20, 30, 40, 50 and 60 days incubation period. Total shoot length was highest in BAP in all incubation periods. Total shoot weight was higher in BAP (2 mg/l) and lower in NAA (0.2 mg/l) as compared to MS medium without hormone. The results showed that BAP at the concentration of 2 mg/l was effective for pineapple shoot growth and development.